PERCEPÇÃO DE AUTO-ESTIMA E QUALIDADE DE VIDA DO JOVEM-ADULTO SURDO UNIVERSITÁRIO - Contieri, Suzana de Mello (2007)
The present work has as its main theme the opinion of deaf university student about his self-esteem and quality of life. The objectives were to know the deaf young university student according to his opinion, trying specifically to identify the factors which have contributed to his psychological development and self-esteem, and also recognize the characteristics of quality of life, taking into account physical and psychological aspects, social relationships and the environment. Three deaf young university students took part in this research which used the qualitative descriptive method, using interviews and WHOQOL-bref as a source of collecting data. The qualitative method in the health area is used to investigate the meaning that some phenomena like feelings, ideas, living experiences and manifestations have in people’s lives, because these phenomena will shape their lives in many aspects including health care. We realized that as they grow older, they are able not only to make decisions, but also to choose their path with leeway due to the experiences and conditions which were presented to them. We verified that the situations lived in the school environment and the opportunity of learning the sign language have contributed to their formation as a subject not limited to their deafness condition. It was possible to identify that they have expectations about their future professional lives and they expressed their difficulties, desire, frustration related to job opportunities, social and family relationships as any other person, finding internal strength to face daily circumstances. The results of the research have also permitted to observe that deaf people recognize the degree of satisfaction they have with their lives, health and with their physical, psychological and social condition. Then we concluded that by retelling the story of their lives, deaf people have the possibility of recognizing themselves as subjects and the opportunity of continuing with their own experiences that have contributed to their welfare